2019
DOI: 10.32539/mks.v51i2.8531
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Risiko Dengan Kejadian Erythema Nodosum Leprosum (Enl) Di Rsup DR Mohammad Hoesin Palembang

Abstract: Erythema Nodosum Leprosum (ENL) adalah komplikasi kusta berupa reaksi hipersensitivitas tipe III dengan peradangan akut karena respon berlebihan tubuh terhadap M. leprae. Diagnosis kasus lebih awal, penanganan yang tepat terhadap reaksi kusta dan identifikasi pasien kusta yang memiliki risiko terjadinya komplikasi adalah sebuah tahapan untuk mencegah kecacatan yang disebabkan oleh kusta. Penelitian ini bertujuan mengidentifikasi dan menganalisis hubungan faktor risiko dengan kejadian Erythema Nodosum Leprosum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
4
0
3
Order By: Relevance
“…Table 1 shows that the participants in this study consisted of 22 male patients (36.7%) and 38 female patients (63.3%). Similar research also reported that the number of chronic renal failure patients at Dr. Mohammad Hoesin Palembang was dominated by female at 169 (56.3%) compared to male at 131 people (43.7%) (Hervinda et al, 2014). Although there were more female patients involved in this study, gender is not a major risk factor for chronic renal failure since it can occur in both men and women.…”
Section: Patient Characteristicssupporting
confidence: 74%
“…Table 1 shows that the participants in this study consisted of 22 male patients (36.7%) and 38 female patients (63.3%). Similar research also reported that the number of chronic renal failure patients at Dr. Mohammad Hoesin Palembang was dominated by female at 169 (56.3%) compared to male at 131 people (43.7%) (Hervinda et al, 2014). Although there were more female patients involved in this study, gender is not a major risk factor for chronic renal failure since it can occur in both men and women.…”
Section: Patient Characteristicssupporting
confidence: 74%
“…CSOM quiet phase is when CSOM does not come out secretariat from the timpani cavity. In addition, CSOM is divided into 2 types, namely safe or benign type and hazard type or malignant (Laisitawati et al, 2017). Here are the differences found in benign type CSOM and malignant type: Based on the table, we can adjust it to the physical examination of CSOM patients who visit at the ENT HN poly at Umbu Rara Meha Hospital.…”
Section: Physical Examination Found To Distinguish Benign Type Csom A...mentioning
confidence: 99%
“…Hal ini ditunjang dari riset yang dilaksanakan (Delima & Tjitra, 2017) yang menunjukkan prevalensi penyakit ginjal meningkat dengan bertambahnya usia. Ditunjang kembali dengan penelitian (Hervinda & Novadian, 2014) mengemukakan bahwa ginjal akan mengalami perubahan anatomi, fisiologi, dan sitologi seiring bertambahnya usia.…”
Section: Karakteristik Responden Berdasarkan Usiaunclassified